1990
DOI: 10.1111/j.1365-2648.1990.tb01886.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education on nurses' perception of AIDS

Abstract: This paper examines changes in health care workers' perceptions of AIDS accruing from attempts at professional enlightenment. Based upon a 4-month study of 60 registered nurses enrolled in a bachelor of nursing programme, it investigates alterations in knowledge and attitudes resulting from intense instruction on AIDS and AIDS patient care as part of a class in epidemiology. Contrary to what much of the literature has suggested to this point regarding knowledge enhancement and attitudinal transformation, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…Institution of appropriate AIDS/HIV educational programmes has the potential to change nurses’ attitudes. For instance, after a four‐month intensive education on AIDS and care of AIDS patients as part of an epidemiology course in a Bachelor of Nursing programme in Canada, nurses’ attitudes towards AIDS and caring for AIDS patients had become significantly more positive 10 . In this study, there was a significant decline (from 83% to 57%) in nursing students expressing concerns regarding treating AIDS patients.…”
Section: Discussionmentioning
confidence: 61%
“…Institution of appropriate AIDS/HIV educational programmes has the potential to change nurses’ attitudes. For instance, after a four‐month intensive education on AIDS and care of AIDS patients as part of an epidemiology course in a Bachelor of Nursing programme in Canada, nurses’ attitudes towards AIDS and caring for AIDS patients had become significantly more positive 10 . In this study, there was a significant decline (from 83% to 57%) in nursing students expressing concerns regarding treating AIDS patients.…”
Section: Discussionmentioning
confidence: 61%
“…The use of educational interventions which adopt an interactive and holistic approach can be successful in improving knowledge and changing attitudes about patients with HIV/AIDS. In a study of 60 registered nurses enrolled in a Bachelor of Nursing programme at the University of Lethbridge in southern Alberta, Canada, it was reported that the nurses were better informed and had more favourable and liberal attitudes towards caring for patients with HIV/AIDS, following completion of intensive education on the subject ( Armstrong‐Esther & Hewitt 1990). In Australia, in a survey of health care professionals, at a Perth paediatric teaching hospital, it was reported that there was a need for educational programmes to concentrate on the personal domain of attitudes to HIV/AIDS and homosexuals, as well as including factual information ( Hunt et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…These have focused primarily on changing knowledge, attitudes and willingness to work with persons with HIV/AIDS (PHAs) (e.g. Armstrong-Esther et al, 1990;Feit et al, 1990). Early models targeted physicians and nurses; this was reflective of the terminal nature of the illness in the 1980s and early 1990s.…”
Section: Introductionmentioning
confidence: 99%